As práticas e as barreiras da ecologia industrial nas primeiras e segundas camadas de fornecimento: survey no setor automotivo brasileiro - Tomé, Ricardo Scherrer (2016)
The process of vehicle assembly in Brazil is led by transnational companies that follow strict quality systems on manufacturing plants. These systems are inserted directly standards related to environmental issues, procedures and audits processes are performed periodically to ensure that the harmful impacts on the environment are minimized. However, what the true extent of environmental practices? What the true extent of environmental practices? Is it possible observe effective controls on manufacturers, due to its structure and power of investment, what about your supply chain? The pressure for lower costs for acquisition of auto parts destined for assembly of vehicles, creates a competitive environment in the supply chain where their members generate great efforts to meet the requirements linked to environmental issues, requirements that can interfere with productivity requiring changes on production processes, high investments in equipment for waste treatment and specialized personnel for implementation and monitoring of requirements relating to environmental protection. In this context, the concept of Industrial Ecology, in order to check out beyond the gates of the manufacturing plants, inside the factories of the first and second tier of suppliers of auto parts, if there are integrated environmental practices. This dissertation conducted a field survey in the first and second tier of parts suppliers called Tier1 and Tier2, if noting that the industrial ecology practices are over-represented in companies Tier 1 than in Tier 2 companies, and the barriers that hinder the adoption of IE practices are more present on suppliers Tier 1 than Tier 2 companies, making it possible to conclude that the pressure from automakers are focused on the Tier 1 suppliers that despite barriers that hinder the adoption of the IE practices, they have three times more practical than its suppliers Tier 2 that limited service internal practices of IE. The methodology used was the survey method in 110 companies in the Brazilian automotive industry and the analysis and discussion of the data were made by means of structural equations using the PLS system.